Peran Guru dalam Upaya Pencegahan Pelecehan Seksual pada Anak Disabilitas Intelektual di SLB Perwari Padang (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the role of teachers in preventing sexual harassment of children with intellectual disabilities at SLB Perwari Padang, including supporting factors, obstacles, and forms of collaboration between schools and parents. The study used a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation with three teachers, one principal, and two parents. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, while data validity was maintained through triangulation and member checking. The results showed that teachers play a role as educators, guides, supervisors, and liaisons between schools and families in efforts to prevent sexual harassment. Prevention is carried out through introductions to body parts and privacy boundaries, the use of visual and concrete media, repetition of material, supervision of student interactions, and the habit of reporting. Supporting factors include school cooperation, principal support, learning media, CCTV, and parental involvement. Meanwhile, the main obstacles include children's limited understanding, communication barriers, poor memory, taboos, and exposure to digital media. This study emphasizes the importance of a simple, repetitive, systematic, and collaborative prevention approach between schools and families.